Beton Geopolimer Sebagai Alternatif Perkerasan Kaku (Rigid Pavement) Ramah Lingkungan - Oktaviastuti, Blima; Leliana, Arinda; Dinar Rahma, Pamela (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Road construction generally uses flexible and rigid bending of the water to cause a decrease ingreen land. This affects the reduction of water catchment areas. The use of Geopolymerconcrete is an environmentally friendly alternative that is expected to be able to disperize waterin the soil. This paper aims to explain the study of: (1) geopolymer concrete; (2) strong press;and (3) geopolymer concrete applications on rigid pavement. Based on the results of the study,it can be concluded that the content of geopolymer concrete is environmentally friendly andminimal manufacturing cost. The implementation of rigid pavement during this time, generallyhas major constraints on costs. Application of the use of geopolymer concrete on rigidpavement, in the future is expected to be the replacement solution of conventional concrete